Nano-Turbulence in Biological Systems: A New Paradigm - Barack Ndenga (Publisher, 2025)
Turbulence has traditionally been considered impossible in nanoscale biological environments due to strong viscous damping and low Reynolds numbers. Here I introduce the concept of nano-turbulence: a novel, coherence-driven, hydrodynamic-like regime emerging from quantum π-field dynamics within biomolecules, particularly proteins. Building on the bio-quantum framework of Quantum π in Biomolecular Dynamics, I show that proteins behave as nano-quantum fluids, supporting internal vortices, coherence eddies, and structured π-flow cascades. This article develops the mathematical foundations of nano-turbulence, characterizes its structural origins (aromatic networks, hydrogen bonds, curvature funnels), and discusses its functional consequences for allostery, mutation sensitivity, catalytic efficiency, and quantum energy transport. To the best of my knowledge, this is the first formal scientific proposal of nano-turbulence as a biological phenomenon, establishing a new paradigm in quantum biophysics. Keywords : Nano-turbulence Quantum Hydrodynamics Quantum π-field Quantum Biology Protein Dynamics Aromatic Networks Allostery Mutation Effects Bio-Quantum π Dynamics Quantum Coherence Nonlinear Biological Dynamics
Nano-Turbulence in Biological Systems: A New Paradigm introduces a novel theoretical framework in which biological macromolecules—particularly proteins—are modeled as quantum-coherent nano-fluids capable of sustaining structured, turbulence-like flow patterns at the nanometer scale. This work builds upon the Quantum π-field formalism and proposes that internal biomolecular dynamics are governed by nonlinear interactions between coherence fields, quantum hydrodynamic velocities, and molecular topology. In this article, I define nano-turbulence as a new class of biological phenomenon characterized by coherence-driven vortices, π-flow instabilities, and nanoscale energy circulation. I develop the mathematical foundation of nano-turbulence, analyze its potential structural origins (aromatic networks, hydrogen-bond clusters, curvature funnels), and propose its biological implications for allostery, mutation sensitivity, catalytic efficiency, and quantum energy transport. To the best of my knowledge, this is the first scientific work to formalize nano-turbulence as a biomolecular behavior arising from π-field dynamics. This establishes a new research direction—Bio-Quantum π Dynamics (BQP Dynamics)—that unifies quantum hydrodynamics, structural biology, and nonlinear biophysics. This deposition includes theoretical content, conceptual figures, and explanatory material illustrating π-vortices, coherence cascades, and mutation-induced π-defects as manifestations of nano-turbulence.